DAMPAK KUALITAS LAYANAN DAN NILAI NASABAH TERHADAP KEPUASAN NASABAH PERBANKAN SYARIAH - Hamdani Hamdani (Jurusan Akuntansi Politeknik Negeri Bandung, 2019)
Abstract: This research refers to studying service quality and customer value towards customer satisfaction in Islamic banking with a case study in PT Bank Syariah Mandiri Lhokseumawe Branch. The data used in this study are primary data through interviews using a questionnaire. The sample in this study was accidental sampling. The research method used is qualitative and quantitative methods, with multiple linear regression analysis. The results released by simultaneous shows, service quality and customer value have a positive and significant influence on customer satisfaction. While the results of the study indicate that, service quality has a positive and significant effect on customer satisfaction, the customer value also has a positive and significant influence on customer satisfaction. From the variable Quality of service and value of customers that are just the same as partial to customer satisfaction in Islamic banking. This research can be used as an evaluation and input for the management of a special sharia banking company, PT Bank Syariah Mandiri, Lhokseumawe Branch, to always improve service quality and value customers receive customers satisfied with services and benefits obtained or obtained by customers. Keywords: Service Quality, Customer Value, Customer Satisfaction